2009
DOI: 10.1136/bmj.b2732
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care in for-profit and not-for-profit nursing homes: systematic review and meta-analysis

Abstract: Objective To compare quality of care in for-profit and notfor-profit nursing homes. Design Systematic review and meta-analysis of observational studies and randomised controlled trials investigating quality of care in for-profit versus not-forprofit nursing homes. Results A comprehensive search yielded 8827 citations, of which 956 were judged appropriate for full text review. Study characteristics and results of 82 articles that met inclusion criteria were summarised, and results for the four most frequently r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
261
4
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(294 citation statements)
references
References 22 publications
24
261
4
5
Order By: Relevance
“…Other studies, however, question this claim. A large meta-study on elderly care in the US has, for instance, suggested that public providers in most cases perform better than commercial providers (Comondore et al 2009). And in 2015, two leading scholars provided a very critical overview of the results of New Public Management reforms in the UK (Hood and Dixon 2015).…”
Section: Welfare Services and User Choicementioning
confidence: 99%
“…Other studies, however, question this claim. A large meta-study on elderly care in the US has, for instance, suggested that public providers in most cases perform better than commercial providers (Comondore et al 2009). And in 2015, two leading scholars provided a very critical overview of the results of New Public Management reforms in the UK (Hood and Dixon 2015).…”
Section: Welfare Services and User Choicementioning
confidence: 99%
“…5 The quality of care and quality of life in NHs has been a long-standing concern of consumers, care providers, and policy makers. 6,7 An increasing body of evidence shows that NH residents commonly experience preventable negative outcomes (eg, adverse drug events, pressure ulcers, falls with injuries, physical and pharmacological restraint use, delirium, and elder abuse) associated with higher morbidity and mortality. 8e14 The World Health Organization, the International Association of Gerontology and Geriatrics, and the Institute of Medicine in the United States emphasize the pressing need for innovative care models to improve the quality of care in NHs.…”
mentioning
confidence: 99%
“…Driven by profit maximizing, for-profit nursing homes have been shown to provide poorer quality compared to non-profit nursing homes [34][35][36][37].…”
Section: Evidence Of Low Quality In Nursing Homes and Changes In Qualmentioning
confidence: 99%